On auditory choreography: How walking anticipates sound and movement resonates. Issue 2 (1st December 2019) - Persyn, Leonie
AbstractBenjamin Vandewalle and Yoann Durant label their performance Hear (2016) as an auditory choreography. Starting from an elaboration on the etymology of choreography I research what the auditory dimension adds and changes to choreography. Choreographing based on auditory decisions inverses sound and movement. This inversion has consequences from the process to the end result. Based on the sonic quality as main decision principle I unravel the creation process of Hear in seven main action: to stand, to walk, to breathe, to look, to move, to disappear and to sound. This division reveals how the actual choreographing doesn't stop at the end of the creation process. In the second half of the paper, I turn to the experience of an auditory choreography, where the body of the audience functions as a resonance box. The discomfort of a blindfold during the experience, leads to the installation of a delicate intimacy and reveals the close connection between sound, touch and movement. The precariousness of the installed intimacy triggers and enforces the audience imagination. Through my own experience of Hear I discover how the audience in an auditory choreography becomes a co-creator.